2011
DOI: 10.7326/0003-4819-155-12-201112200-00004
|View full text |Cite
|
Sign up to set email alerts
|

New Insights About Vitamin D and Cardiovascular Disease

Abstract: The worsening worldwide trend toward nutritional insufficiency and the emerging knowledge of the nonhormonal actions of vitamin D and its metabolites have increased interest in the synthesis, metabolism, and action of vitamin D. Vitamin D deficiency has been linked with hypertension, myocardial infarction, and stroke, as well as other cardiovascular-related diseases, such as diabetes, congestive heart failure, peripheral vascular disease, atherosclerosis, and endothelial dysfunction. This review discusses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
131
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 74 publications
0
131
0
4
Order By: Relevance
“…32 In this context, our findings assume particular relevance as they were derived from a relatively healthy disease-free cohort after rigorous exclusion of individuals with confounding comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…32 In this context, our findings assume particular relevance as they were derived from a relatively healthy disease-free cohort after rigorous exclusion of individuals with confounding comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The classical risk factors for CVD are diabetes, hypertension, dyslipidemia, smoking, body mass Index (BMI), sedentary lifestyle, chronic inflammation and taking DMARDs 77,78 . Recent data, showed that deficiency of vitamin D is related to the poor endothelial function and the development of atherosclerotic plate, leading to an additional burden factor for CVD in the population 79 . According to the above, and considering the aggravating role of vitamin D on systemic inflammation, we could argue that people with AS which have deficiency in vitamin D have higher possibility to be diseased with CVD compared to the general population.…”
Section: Vitamin D and Common Comorbidities In As Patientsmentioning
confidence: 99%
“…Durante las dos últimas décadas, un gran número de estudios se han centrado en investigar las funciones biológicas de la VD y su nivel sanguíneo óptimo, encontrando una correlación positiva entre la deficiencia de VD con los tres problemas de salud más prevalentes en el mundo: enfermedad cardiovascular, cáncer y enfermedades respiratorias (7)(8)(9). Aunque anteriormente se consideró que la deficiencia de esta vitamina era un problema común sólo de los países que carecían de un clima soleado la mayor parte del año, los resultados de investigación confirman cada vez más que la deficiencia de VD es un problema de salud pública (10), incluso en países que disfrutan de una temperatura cálida la mayor parte del año (11).…”
Section: Introductionunclassified